THE ACUTE TOXICITY AND BONE-MERROW MICRONUCLEUS TESTS OF WATER EXTRACT FROM Avicennia marina FRUITS IN MICE - Gao Xiu-mei; Han Wei-Dong; Yu Zen-ji (JOURNAL OF COASTAL DEVELOPMENT, 2008)
The acute toxicity and mutagenesis of water extract from Avicennia marina fruits in mice were studiedwith the oral acute toxicity test according to Karber’s method and the bone-marrow micronucleus testfor mutagenic observation.The results showed the water extract from A. marina fruits presented theacuteper oral toxicity at LD50 >10.000 mg/kg; the bone-marrow nicrobucleus test indicated no mutageniceffects. Water extract from A.Marina fruits belong to non toxic compounds and has no mutagenic effectsunder the experimental conditions.